Melanotic macules of the penis. A case report - Elizabet Fernández López; Noelvis Hernández Bacallao; Daymí Martínez Rodríguez; Adialys Acosta Rodríguez (Medisur)
Melanotic macules of the penis are idiopathic, benign, rare lesions, sometimes multifocal, heterochromic and irregular, which must be differentiated from mucosal melanoma. A patient with asymptomatic pigmented lesions on the penis, but which had increased in number is presented. With dermoscopy and histopathology test, the diagnosis of melanotic macules of the penis was reached. Although the therapeutic options in the described environment are limited, the significance of this dermatosis diagnosis lies in ruling out the possibility of its malignancy.